21. Dnevi varstvoslovja, Ljubljana, 3. junij 2020: Zbornik povzetkov - Marina Bajić; Modic, Maja; Areh, Igor; Flander , Benjamin; Lobnikar , Branko; Pavšič Mrevlje , Tinkara (2020)
The 21st Conference Days of Criminal Justice and Security, 3rd of June 2020: Book of Abstracts. Contributions of the 21st Conference Days of Criminal Justice and Security represent professional and scientific consideration of paths and resources for provision of security in contemporary society. The book of abstracts includes abstracts of four round tables and thirty-five contributions, dealing with a broad range of topics such as cyber security, plural policing, prevention and recognition of radicalization, security and safety in local communities, various forms of violence, criminal investigation, criminology, fundamental rights in police procedures, police oversight, criminal justice and security terminology, private detective activities, the implementation of criminal sanctions, technologies in the security provision, and other current security challenges of contemporary society.
Keywords: Days of criminal justice and security; criminal justice and security; security, safety and security in local communities; policing; criminology; criminalistics; information security; penology; radicalization; private detective services